Credo in unam naturam - Powell, Kit, 1937- (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1998)
Recording of Kit Powell's Credo in unam naturam. This work is an homage to the natural world as well as a work of nostalgia for the composers home country, New Zealand. Sound materials of birds (Kiwi, Bellbird, Fantail, and Little Grey Warbler) as well as a Humpback whale can be heard.